2017
DOI: 10.5761/atcs.nm.16-00220
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Thymectomy with Tangential Partial Resection of the Innominate Vein

Abstract: We herein report a case in which thoracoscopic thymectomy with partial resection of the brachiocephalic vein was performed using a subxiphoid approach. We suggest the usefulness of the subxiphoid approach in thymectomy. We could extend the indications of thoracoscopic thymectomy for invasive tumors. Thoracoscopic thymectomy with the combined resection of part of the brachiocephalic vein was possible. The pathological diagnosis of the tumor was diffuse large cell B-cell lymphoma. Since the postoperative complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…Finalmente, Naito et al [19], Tsuboi et al [4], Zhang et al [20] y Yano et al [21] reportaron casos de timomas con abordaje terapéutico quirúrgico similar al de nuestro paciente, es decir timectomía a través de la videotoracoscopia. Tsuboi et al, presenta el caso de un timoma tipo B1, estadio I de Masaoka, en una paciente con degeneración espinocerebelosa, tratada con resección quirúrgica mediante cirugía videotoracoscópica, sin recurrencia en 3 años de seguimiento [4].…”
Section: Información De Los Autoresunclassified
See 2 more Smart Citations
“…Finalmente, Naito et al [19], Tsuboi et al [4], Zhang et al [20] y Yano et al [21] reportaron casos de timomas con abordaje terapéutico quirúrgico similar al de nuestro paciente, es decir timectomía a través de la videotoracoscopia. Tsuboi et al, presenta el caso de un timoma tipo B1, estadio I de Masaoka, en una paciente con degeneración espinocerebelosa, tratada con resección quirúrgica mediante cirugía videotoracoscópica, sin recurrencia en 3 años de seguimiento [4].…”
Section: Información De Los Autoresunclassified
“…Zhang et al, describen el caso de un timoma tipo B3, en forma de mancuerna detrás de la vena innominada izquierda, tratado únicamente con timectomía extendida toracoscópica transsubxifoidea asistida por robot, con seguimiento en un año sin recurrencias [20]. Asimismo, Yano et al, exponen el caso de una timectomía toracoscópica con resección parcial de la vena braquiocefálica con abordaje subxifoideo, pero adicionalmente se le administró quimioterapia adyuvante al paciente [21]. Estos reportes demuestran que se puede disminuir la invasividad de la cirugía utilizando dichos procedimientos sin esternotomía, con resultados eficaces [4,[20][21].…”
Section: Información De Los Autoresunclassified
See 1 more Smart Citation
“…More recently, several groups have reported surgical techniques for treating cases of advanced thymoma with VATS. Hirai et al introduced a method that combines video-assisted thoracoscopic thymectomy (VAT-T) with lateral thoracotomy for stage II and some stage III thymomas with local lung and/or pericardium invasion, and Yano et al reported a case in which a thoracoscopic thymectomy with partial resection of the brachiocephalic vein (BCV) was performed by use of a subxiphoid approach (11,12). Quite recently, a retractor with a gas insufflation tube and multiple access ports was developed, and shown able to create a wide surgical view and space, thus providing easier surgical manipulation.…”
Section: Mis For Advanced Thymomamentioning
confidence: 99%
“…W e have previously suggested the usefulness of the subxiphoid approach in thymectomy. [1][2][3][4] We recently expanded the indications of thoracoscopic thymectomy to include large thymic cystic lesions. Surgeons have hesitated to perform thoracoscopic thymectomy for large thymic cystic lesions because of the possibility of intraoperative rupture of the cystic lesions.…”
mentioning
confidence: 99%